## Trending News

Promoted

# Solve 4[x-(3-2x)]+5=3(x+11)?

Please help! Solve 4[x-(3-2x)]+5=3(x+11)

### 5 Answers

Relevance

- DavidLv 79 years agoFavorite Answer
4[x - (3 - 2x)] + 5 = 3(x + 11)

4[x - 3 + 2x] + 5 = 3x + 33

4[3x - 3] = 3x + 28

12x - 12 = 3x + 28

9x = 40

x = 40/9

- TaylorLv 59 years ago
The first thing you want to do is get rid of all the brackets.

4[x -(3-2x)]+5 = 3(x+11)

4[x-3+2x]+5 = 3x + 33

4x-12+8x+5 = 3x+33

4x+8x-3x = 33-5+12

9x = 40

Then divide both sides by 9 to solve for x.

- Anonymous9 years ago
4[-3 - x] + 5 = 3x + 33

-12 - 4x + 5 = 3x + 33

Now, we combine the like terms!

-7 = 7x + 33

-40 = 7x

x = -5.71

- How do you think about the answers? You can sign in to vote the answer.
- 9 years ago
4[x-(3-2x)]+5=3x+33

4[x-3+2x]+5=3x+33

4[3x-3]+5=3x+33

12x-12+5=3x+33

12x-7=3x+33

9x=40

x=40/9

Still have questions? Get your answers by asking now.